Contemporary aesthetic perspectives on imagination and reality media - Manera, Lorenzo (Aesthetica Preprint, 2023)
The growing and ubiquitous presence of ‘digital reality media’, meaning technological devices that do not rely either on inner visualization or imagination – such as Augmented and Virtual Reality devices and 360º video (Engberg & Bolter 2020) – raises several issues. Such issues are related to the role played by the imaginative faculties both within emerging visual-motor and perceptive configurations and within the transformative process of remediation instantiated by the virtualization of reality. This contribution aims firstly to discuss the concepts of second-order media and reality media (Bolter, Engberg & MacIntyre 2021) by linking them to Pinotti’s concept of an-iconology (Pinotti 2021). By drawing on Tavinor’s digital aesthetics (Tavinor 2022), this contribution argues that the an-iconic condition of VR media might be better intended as a desirable outcome in current research, rather than a condition already achieved. In order to discuss whether the imaginative aspects and those that define the use of digital devices are characterized by an interactive statute, this contribution addresses Montani’s notion of ‘intermedial imagination’ (Montani 2022) and Flusser’s concept of Technoimagination (Flusser 2008). Thirdly, this paper discusses how the interactive concept of imagination – suggested by the re-definition of the relationship between distance and materiality, provenance and pertinence – is displayed differently in VR and AR. Finally, the contribution faces the topic of the fallout that the most recent technological development (in terms of reality media), such as BCI (brain computer interface), might have on human imaginative faculties.